Question
upstudy study bank question image url

\( 6 x-y-4=0 \) and \( 9 x+1=-2 y \)

Ask by Gray Savage. in South Africa
Feb 20,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

\( x=\frac{1}{3} \) and \( y=-2 \).

Solution

Solve the system of equations \( 6x-y-4=0;9x+1=-2y \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}6x-y-4=0\\9x+1=-2y\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}y=6x-4\\9x+1=-2y\end{array}\right.\) - step2: Substitute the value of \(y:\) \(9x+1=-2\left(6x-4\right)\) - step3: Expand the expression: \(9x+1=-12x+8\) - step4: Move the expression to the left side: \(9x+12x=8-1\) - step5: Add and subtract: \(21x=8-1\) - step6: Add and subtract: \(21x=7\) - step7: Divide both sides: \(\frac{21x}{21}=\frac{7}{21}\) - step8: Divide the numbers: \(x=\frac{1}{3}\) - step9: Substitute the value of \(x:\) \(y=6\times \frac{1}{3}-4\) - step10: Substitute back: \(y=6\times 3^{-1}-4\) - step11: Calculate: \(y=-2\) - step12: Calculate: \(\left\{ \begin{array}{l}x=\frac{1}{3}\\y=-2\end{array}\right.\) - step13: Check the solution: \(\left\{ \begin{array}{l}x=\frac{1}{3}\\y=-2\end{array}\right.\) - step14: Rewrite: \(\left(x,y\right) = \left(\frac{1}{3},-2\right)\) The solution to the system of equations \(6x-y-4=0\) and \(9x+1=-2y\) is \(x=\frac{1}{3}\) and \(y=-2\).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

To solve the equations \( 6x - y - 4 = 0 \) and \( 9x + 1 = -2y \), let's first rearrange them into a more convenient form for solving. The first equation can be rewritten as \( y = 6x - 4 \). For the second equation, rearranging gives \( 2y = -9x - 1 \) or \( y = -\frac{9}{2}x - \frac{1}{2} \). Now we set the right-hand sides equal to each other: \( 6x - 4 = -\frac{9}{2}x - \frac{1}{2} \). Multiplying everything by 2 to eliminate the fraction yields: \( 12x - 8 = -9x - 1 \). Adding \( 9x \) to both sides gives: \( 21x - 8 = -1 \). Adding 8 to both sides results in \( 21x = 7 \), thus \( x = \frac{1}{3} \). Substituting \( x \) back into the first equation to find \( y \): \( y = 6\left(\frac{1}{3}\right) - 4 = 2 - 4 = -2 \). So the solution for the equations is \( x = \frac{1}{3} \) and \( y = -2 \). Enjoy checking the solution by substituting back into both original equations!

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy